THE DEVELOPMENT OF E-GOVERNANCE-BASED QUALITY IN THE UNIVERSITIES - Anuar Sanusi; Yulmaini -; M. Ariza Eka Yusendra; Andi Desfiandi (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Universities hold a strategic role in society as the teaching university, the research university, and the bastion of civilization. In this decade, the challenges of the universities become more complex where a paradigm shift in the universities occur such as: (1) the shifting of the role of the universities due to the influence of the globalization; (2) the scarcity of resources in response to changes with the proper way; (3) the development of the science and technology which accelerates rapidly; and (4) the development of the rapid entrepreneurial culture. Some important and fundamental issues facing the universities college in Indonesia today is that the existence of the universities college in Indonesia still faces a number of obstacles in the policy, the implementation, the monitoring, and the evaluation. Moreover, the issue of quality and the relevance of outputs of the universities have not contributed optimally in the world of industry and society. The universities have not optimally been able to become the important sectorwhich can produce a significant number of entrepreneurs with the orientation of job creation and self-reliance. Based on the background of this grant research above, it can be concluded that the strategy of private universities towards the world class or high quality is studied. The method used was a qualitative research consisting of studying literature, conducting interviews, and distributing questionnaires to the informants in the universities in four provinces or cities in the area of The coordinator of The Private UniversitiesII of the southern sumatra and the analysis models. The following method used a quantitative method to measure the parameters of the performance of the universities and entrepreneurial growths of the universities. According to the results of the research in the first, second, and third year, a model to improve the e-governance-based quality to the universities through the research focus, the entrepreneurship, and the development of the resources was developed in the area of The coordinator of The Private Universities II of the southern sumatra. The final result of the improvement of e-governance-based quality in the universities in southern sumatra was the manifestation of the policy of the ministry of the higher education and research in implementing the management of the world-class universities, the scientific publications, and the reference textbooks. KEYWORDS: Quality, E-Governance, Research, Enterprise and Development